2020
DOI: 10.1038/s41598-020-78523-8
|View full text |Cite
|
Sign up to set email alerts
|

Dermal fibroblast-like cells reprogrammed directly from adipocytes in mouse

Abstract: In deep burns, early wound closure is important for healing, and skin grafting is mainly used for wound closure. However, it is difficult to achieve early wound closure in extensive total body surface area deep burns due to the lack of donor sites. Dermal fibroblasts, responsible for dermis formation, may be lost in deep burns. However, fat layers composed of adipocytes, lying underneath the dermis, are retained even in such cases. Direct reprogramming is a novel method for directly reprograming some cells int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…DTG and ELV were more capable in this activity. This last result acquires high relevance considering recent reports showing that forced expression of PPAR is able and sufficient to induce adipogenesis in fibroblasts [36] and that adipocytes can be reprogrammed into fibroblasts under transfection of some master regulators [38]. More recently, Jones et al [59] demonstrated that adipocytes could acquire a fibroblast-like transcriptional signature under over-feeding conditions.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…DTG and ELV were more capable in this activity. This last result acquires high relevance considering recent reports showing that forced expression of PPAR is able and sufficient to induce adipogenesis in fibroblasts [36] and that adipocytes can be reprogrammed into fibroblasts under transfection of some master regulators [38]. More recently, Jones et al [59] demonstrated that adipocytes could acquire a fibroblast-like transcriptional signature under over-feeding conditions.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, in the last 20 years, some studies reported increased fibrosis in adipose tissue from PWH [34][35][36], and several mechanisms have been hypothesized. It has been described the increase of extracellular matrix in adipose tissue by deposition of collagen produced by adipocytes [35,37] and the reprogramming of adipocytes into fibroblast, confirmed by the expression of ER-TR7, a fibroblastic marker [38]. In addition, Ngono Ayissi et al [39] described the ability of BIC and DTG to induce a pro-fibrotic phenotype in simian beige adipose tissue and found this phenotype to be associated with insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…DTG and EVT were more efficient in this activity. This last result acquires high relevance considering recent reports showing that forced expression of PPARɣ is able and sufficient to induce adipogenesis in fibroblasts [36] and that adipocytes can be reprogrammed into fibroblasts under transfection of some master regulators [38]. More recently, Jones et al demonstrated that adipocytes could acquire a fibroblast-like transcriptional signature by using a murine animal model under over-feeding conditions [50].…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, in the last 20 years, some studies reported increased fibrosis in adipose tissue from HIV-infected patients [34-36], and several mechanisms have been hypothesized to explain this phenomenon. It has been described the increase of extracellular matrix in adipose tissue by deposition of collagen produced by adipocytes [35, 37] and the reprogramming of adipocytes into fibroblast, confirmed by the expression of ER-TR7, a well-known fibroblastic marker was also reported [38]. In addition, more recently, Ngono et al described the ability of BIC and DTG to induce a pro-fibrotic phenotype in simian beige adipose tissue and found this phenotype to be associated with insulin resistance [39].…”
Section: Introductionmentioning
confidence: 99%